Group portrait of four women in a bar - Sahl, Ted (photographer):::Creator::::::::::::
Photograph shows a group portrait of four women in a bar. The woman on the far right has her left arm resting on the woman next to her and her hand is reaching toward the third woman. In her right hand there is a drinking glass. The fourth woman is standing next to the third with her hands in her pocket. Bottles of alcohol are visible behind them.